2018
DOI: 10.1002/jpln.201700575
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza enhances nutrient accumulation in wheat exposed to elevated CO2 and soil salinity

Abstract: Plant can establish a mutualistic symbiosis with arbuscular mycorrhizal (AM) fungi to improve plant growth and resistance to environmental stresses. The aim of this study was to evaluate the effect of AM on nutrient accumulation of wheat (Triticum aestivum L.) plants under combined elevated CO2 and soil salinity. The effects of CO2 elevation (700 ppm) and salt treatments (0, 1, and 2 g NaCl kg−1 dry soil) on the nutrient accumulation of wheat plants inoculated with AM fungus (Rhizophagus irregularis) were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The results advocate that in tropical rice soils, eCO 2 amplified C accumulation in the soil, which possibly stimulates growth of N fixing bacteria and thereby higher available N (Das et al 2011). In wheat, a mutualistic symbiosis with arbuscular mycorrhizal increased carbohydrate and nutrient accumulation in plants exposed to eCO 2 and salinity (Zhu et al 2018b). Thus, looking at the impact of climate change on below ground traits and linking these with processes of nutrient absorption and accumulation seems like a promising line of research for future studies.…”
Section: Plant Molecular and Physiological Responses To Climate Changmentioning
confidence: 66%
“…The results advocate that in tropical rice soils, eCO 2 amplified C accumulation in the soil, which possibly stimulates growth of N fixing bacteria and thereby higher available N (Das et al 2011). In wheat, a mutualistic symbiosis with arbuscular mycorrhizal increased carbohydrate and nutrient accumulation in plants exposed to eCO 2 and salinity (Zhu et al 2018b). Thus, looking at the impact of climate change on below ground traits and linking these with processes of nutrient absorption and accumulation seems like a promising line of research for future studies.…”
Section: Plant Molecular and Physiological Responses To Climate Changmentioning
confidence: 66%
“…During salt stress, sucrose undergoes decomposition in order to meet the requirement of glucose (Geigenberger and Stitt, 1993). Salt stress induced TSS accumulation is further enhanced by AM symbiosis (Talaat and Shawky, 2011; Liu et al, 2016; Garg and Bharti, 2018; Zhu et al, 2018). The higher accumulation of TSS in M plants has been credited to – (i) higher photosynthetic efficiency; (ii) higher activities of α- and β-amylases, SS, and AI; (iii) higher organic acid content; and (iv) carbon requirement of AMF (Garg and Baher, 2013; Yu et al, 2015; Zhu et al, 2016, 2018).…”
Section: Mechanisms Of Salt Tolerance In M Plantsmentioning
confidence: 99%
“…Salt stress induced TSS accumulation is further enhanced by AM symbiosis (Talaat and Shawky, 2011; Liu et al, 2016; Garg and Bharti, 2018; Zhu et al, 2018). The higher accumulation of TSS in M plants has been credited to – (i) higher photosynthetic efficiency; (ii) higher activities of α- and β-amylases, SS, and AI; (iii) higher organic acid content; and (iv) carbon requirement of AMF (Garg and Baher, 2013; Yu et al, 2015; Zhu et al, 2016, 2018). Garg and Bharti (2018) reported that salt tolerant M Cicer arietinum cultivar (PBG 5) accumulated more sugars than its salt sensitive M counterparts (BG256) indicating that accumulation of TSS can enhance tolerance to salt stress.…”
Section: Mechanisms Of Salt Tolerance In M Plantsmentioning
confidence: 99%
“…Moreover, AM plants have been found to have improved plant N and C accumulation and distribution under salinity stress (Evelin et al 2009). In wheat plants, AM has been reported to alleviate the negative effects of salinity by improving nutrient uptake and translocation (Zhu et al 2016(Zhu et al , 2018a. For instance, studies have shown that AM can mitigate the negative effects of salinity stress in wheat plants, both in the field and in greenhouses (Daei et al 2009;Talaat & Shawky 2014;Mardukhi et al 2015;Fileccia et al 2017;Zhu et al 2018b).…”
Section: Introductionmentioning
confidence: 99%